Characterization of cardiac fibroblast-extracellular matrix crosstalk across developmental ages provides insight into age-related changes in cardiac repair - Perreault, Luke R.; Daley, Mark C.; Watson, Matthew C.; Rastogi, Sagar; Jaiganesh, Ajith; Porter, Elizabeth C.; Duffy, Breanna M.; Black, Lauren D. (Frontiers in Cell and Developmental Biology, 2024)
Heart failure afflicts an estimated 6.5 million people in the United States, driven largely by incidents of coronary heart disease (CHD). CHD leads to heart failure due to the inability of adult myocardial tissue to regenerate after myocardial infarction (MI). Instead, immune cells and resident cardiac fibroblasts (CFs), the cells responsible for the maintenance of cardiac extracellular matrix (cECM), drive an inflammatory wound healing response, which leads to fibrotic scar tissue.However, fibrosis is reduced in fetal and early (<1-week-old) neonatal mammals, which exhibit a transient capability for regenerative tissue remodeling. Recent work by our laboratory and others suggests this is in-part due to compositional differences in cECM and functional differences in CFs with respect to developmental age. Specifically, fetal cECM and CFs appear to mitigate functional loss in MI models and engineered cardiac tissues, compared to adult CFs and cECM.We conducted 2D studies of CFs on solubilized fetal and adult cECM to investigate whether these age-specific functional differences are synergistic with respect to impact on CF phenotype, and therefore cardiac wound healing. We found that CF migration rate and stiffness varies with respect to cell and cECM developmental age, and that CF transition to a fibrotic phenotype can be partially attenuated on fetal cECM. However, this effect was not observed when cells are treated with cytokine TGF-β1, suggesting inflammatory signaling factors are the dominant driver of fibroblast phenotype. This information may be valuable for targeted therapies aimed at modifying CF wound healing response, and broadly applicable to age-related studies of cardiac remodeling.